The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.4103/0972-2327.44556
|View full text |Cite
|
Sign up to set email alerts
|

Hyperacute thrombolysis with recombinant tissue plasminogen activator of acute ischemic stroke: Feasibility and effectivity from an Indian perspective

Abstract: Given the constraints of resources, thrombolysis for acute ischemic stroke (AIS) is under evaluation in developing countries like India, especially in areas such as western Utter Pradesh, where it is overly crowded and there is poor affordability.Aim:This study was done to evaluate recombinant tissue plasminogen activator r-tpa in acute ischemic stroke in hyper acute phase, in selected patients of western Utter Pradesh, in terms of feasibility and effectivity.Design:Open, non randomized study.Materials and Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
14
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 13 publications
3
14
1
Order By: Relevance
“…9 In 3 studies from developing countries the mortality at discharge ranged from 0 to 5.9%. 13,14,16 It is estimated that <2% of patients with ischaemic stroke in our hospital drainage area received thrombolysis, which seems comparable with data from other developing countries. 15,16 However, our reported thrombolysis rate is an overestimation for the general population, as most patients with acute stroke are managed conservatively at lower level facilities where thrombolysis is not available.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…9 In 3 studies from developing countries the mortality at discharge ranged from 0 to 5.9%. 13,14,16 It is estimated that <2% of patients with ischaemic stroke in our hospital drainage area received thrombolysis, which seems comparable with data from other developing countries. 15,16 However, our reported thrombolysis rate is an overestimation for the general population, as most patients with acute stroke are managed conservatively at lower level facilities where thrombolysis is not available.…”
Section: Discussionsupporting
confidence: 85%
“…9 Pooled data from five observational studies from developing countries show a lower proportion of patients suffering SICH, 9/293 (3.1%), but the rates ranged from 0 to 5.9% between the different centres. [13][14][15][16][17] Although the number is small and does not represent a significant association, all three of our patients over the age of 75 had bleeding complications. Studies in the developed world support the safety of tPA in patients over 80 years.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…A recent systematic review 17 assessed the global use of rtPA for AIS among 214 countries and found that only 54 (25%) of these countries reported its administration, ranging from as low as 3% (1 of 36) of low-income, to 13% (7 of 54) of lower middle-income, to 28% (15 of 54) of upper middle-income, and to 44% (31 of 70) of highincome countries. 17 In comparison, access to rtPA in Iran is lower than in most of the developed countries [18][19][20][21][22][23][24][25] but comparable with other developing countries [26][27][28][29][30][31][32] ( Fig 2). The barriers of timely administration of rtPA in developing countries include limited resources, prehospital delay, sparse numbers of stroke units, 16,33 poor stroke awareness in the general population, 33 lack of general knowledge and professional education, 33,34 the high cost of rtPA, lack of insurance coverage, low socioeconomic status of patients, 16,33 and physician reluctance and concerns about the benefits compared with its serious side effects, especially bleeding.…”
Section: Discussionmentioning
confidence: 85%